"Spaghetti twisting" technique: a novel method of catching pacemaker leads using a needle's eye snare. Issue 8 (23rd June 2017) - Isawa, Tsuyoshi; Yamada, Takashi; Honda, Taku; Yamaya, Kazuhiro; Ootomo, Tatsushi
Key Clinical Message: The needle's eye snare has become an indispensable tool in contemporary pacemaker lead extraction techniques. Here, we present a modified method of using the needle's eye snare, named "spaghetti twisting" technique, to catch and secure pacemaker leads, which would help operators catch and secure leads much easily. Abstract : The needle's eye snare has become an indispensable tool in contemporary pacemaker lead extraction techniques. Here, we present a modified method of using the needle's eye snare, named "spaghetti twisting" technique, to catch and secure pacemaker leads, which would help operators catch and secure leads much easily.